2020
DOI: 10.1038/s41598-020-67866-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of somatosensory detour circuits mediates functional recovery following dorsal column injury

Abstract: Anatomically incomplete spinal cord injuries can be followed by functional recovery mediated, in part, by the formation of intraspinal detour circuits. Here, we show that adult mice recover tactile and proprioceptive function following a unilateral dorsal column lesion. We therefore investigated the basis of this recovery and focused on the plasticity of the dorsal column-medial lemniscus pathway. We show that ascending dorsal root ganglion (DRG) axons branch in the spinal grey matter and substantially increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The unmyelinated population is thought to directly mediate transmission from nociceptors; injection of capsaicin in rats showed a decrease in the number of unmyelinated fibers in both gracile and cuneate fasciculi (Patterson et al, 1992). These fasciculi are responsible for transmitting information regarding discriminatory touch (Kitai & Weinberg, 1968), deep pressure (Loutit & Potas, 2020), proprioception (Granier et al, 2020), and vibration (Shintani et al, 2000). Indeed, lesions to the dorsal column have led to deficits in some or all of the above functions.…”
Section: General Description Of Human Spinal Cord Anatomymentioning
confidence: 99%
“…The unmyelinated population is thought to directly mediate transmission from nociceptors; injection of capsaicin in rats showed a decrease in the number of unmyelinated fibers in both gracile and cuneate fasciculi (Patterson et al, 1992). These fasciculi are responsible for transmitting information regarding discriminatory touch (Kitai & Weinberg, 1968), deep pressure (Loutit & Potas, 2020), proprioception (Granier et al, 2020), and vibration (Shintani et al, 2000). Indeed, lesions to the dorsal column have led to deficits in some or all of the above functions.…”
Section: General Description Of Human Spinal Cord Anatomymentioning
confidence: 99%
“…Dorsal hemisection, which suppress half of sensory inputs ascending to brain centers, has dramatic acute effects on locomotion, affecting notably paw placing during skilled walking, until sensory afferent reorganization within the ipsilesional hemicord occurs and allows functional recovery. In mice with such lesions, ascending dorsal root neurons increased branching below the lesion site and, in particular, connected propriospinal INs projecting into the cuneate nucleus, constituting so a detour circuit to brainstem centers (Granier et al, 2020), and beyond, to the primary sensory-motor cortex (as afore suggested in rats and monkeys; Kaas et al, 2008). Functional restoration of bilateral tactile and proprioceptive sensation occurred in these animals within weeks, demonstrating the exceptional ability of sensory systems to compensate for selective alterations of their central pathways.…”
Section: Unilateral Spinal Cord Injury-induced Spinal Pathway Plasticitymentioning
confidence: 99%
“…Mainly in these studies, in order to study the somatosensory tract plasticity, the authors performed dorsal column injury. In this model, lemniscal tracts show an impressive ability to sprout and regrow and more importantly, to form functional synapses [17,18].…”
Section: Intrinsic Regrowth Abilities Of the Descending And Ascending Fibers After Scimentioning
confidence: 99%